Arsenic Resistance in Halobacterium sp. Strain NRC-1 Examined by Using an Improved Gene Knockout System - Wang, Gejiao (American Society for Microbiology, 2004)
The genome sequence of Halobacterium sp. strain NRC-1 encodes genes homologous to those responsible for conferring resistance to arsenic. These genes occur on both the large extrachromosomal replicon pNRC100 (arsADRC and arsR2M) and on the chromosome (arsB). We studied the role of these ars genes in arsenic resistance genetically by construction of gene knockouts. Deletion of the arsADRC gene cluster in a Halobacterium NRC-1 Δura3 strain resulted in increased sensitivity to arsenite and antimonite but not arsenate. In contrast, knockout of the chromosomal arsB gene did not show significantly increased sensitivity to arsenite or arsenate. We also found that knockout of the arsM gene produced sensitivity to arsenite, suggesting a second novel mechanism of arsenic resistance involving a putative arsenite(III)-methyltransferase. These results indicate that Halobacterium sp. strain NRC-1 contains an arsenite and antimonite extrusion system with significant differences from bacterial counterparts. Deletion analysis was facilitated by an improved method for gene knockouts/replacements in Halobacterium that relies on both selection and counterselection of ura3 using a uracil dropout medium and 5-fluoroorotic acid. The arsenite and antimonite resistance elements were shown to be regulated, with resistance to arsenic in the wild type inducible by exposure to a sublethal concentration of the metal. Northern hybridization and reverse transcription-PCR analyses showed that arsA, arsD, arsR, arsM, arsC, and arsB, but not arsR2, are inducible by arsenite and antimonite. We discuss novel aspects of arsenic resistance in this halophilic archaeon and technical improvements in our capability for gene knockouts in the genome.